2013
DOI: 10.1021/nl401378r
|View full text |Cite
|
Sign up to set email alerts
|

Fluctuation-Driven Anisotropic Assembly in Nanoscale Systems

Abstract: We demonstrate that the self-assembly of spherical nanoparticles (NPs), grafted isotropically with polymeric ligands, into anisotropic structures is a manifestation of the fluctuations inherent in small number statistics. Computer simulations show that the organization of ligand atoms around an individual NP is not spatially isotropic for small numbers of grafts and ligand monomers. This inherent, spatially asymmetric ligand distribution causes the effective, two-body inter-NP potential to have a strong orient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
83
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 60 publications
(87 citation statements)
references
References 32 publications
3
83
0
Order By: Relevance
“…In this context, studies by Bozorgui et al, 141 Lane and Grest, 110 and Chakravarty et al 151 clearly show that polymer chains do not "uniformly" cover the NP, even in the hypothetical limit where the graft points are randomly distributed on the surface (Fig. 2).…”
Section: Grafted Nanoparticlesmentioning
confidence: 95%
See 1 more Smart Citation
“…In this context, studies by Bozorgui et al, 141 Lane and Grest, 110 and Chakravarty et al 151 clearly show that polymer chains do not "uniformly" cover the NP, even in the hypothetical limit where the graft points are randomly distributed on the surface (Fig. 2).…”
Section: Grafted Nanoparticlesmentioning
confidence: 95%
“…Even in the case of uniform grafting sites, the conformational fluctuations of the small number of polymer chains ensure that the NPs are frequently anisotropically covered by the polymer corona. 141 This fact has been shown to strongly impact the self-assembled NP structures that form. Below, we outline some outstanding issues in this regard.…”
Section: Synthesis Of Nanoparticlesmentioning
confidence: 99%
“…Both experiments 198 and simulations 199 have shown that these grafted nanoparticles robustly self-assemble into a variety of superstructures that are anisotropic typically observed only in systems of anisotropically interacting units. This result, which stems from the deformability of the polymeric corona, holds for both homogeneously and inhomogeneously grafted units at low and intermediate grafting densities.…”
Section: Polymer-based Systemsmentioning
confidence: 99%
“…[34][35][36][37][38] Several approaches have been developed to derive and optimize CG forcefields. [39][40][41][42][43][44][45] Among these, the iterative Boltzmann inversion (IBI) method 39 has become a popular choice due to its straightforward nature, general applicability to a wide range of systems, and basis in structural properties. The IBI method relies on self-consistently adjusting a given potential to achieve convergence with target structural data; for nonbonded interactions this target data takes the form of the radial distribution function (RDF) between interaction sites and the potential is iteratively updated according to…”
Section: Introductionmentioning
confidence: 99%